PERAN AKTOR DALAM FORMULASI KEBIJAKAN MAMI PAPI (MALL MINI PELAYANAN PUBLIK) DI KECAMATAN PARUNG - Wisnu Tri Wibowo (2023)
This research aims to determine the policy formulation process for MAMI PAPI (Public Service Mini Mall) in Parung District and the role of the actors involved in the policy formulation process. And I also want to know the driving and inhibiting factors in formulating the MAMI PAPI (Public Service Mini Mall) policy. This research uses Budi Winarno's theory of public policy formulation. The research method used is qualitative descriptive research. The results of this research show that at the problem formulation stage there are three problems. However, in the problem formulation process we have not been able to identify what kind of public service program will be created. In the policy agenda, the actors involved are from the sub-district head, forwarded to the sub-district secretary, then to the Head of the General and Personnel Section, PLT, Head of the Economic and Development Section, Parung Subdistrict, then down to the Head of the Task Implementation Unit, Parung Subdistrict. Once the concept feels mature, then invite vertical agencies to join. In the search for alternative policies, there is only one alternative, namely the integration of services in one place. In the determination stage, the public service mall policy was launched in January 2020. In the formulation of the MAMI PAPI policy in Parung District, the role of the sub-district head is very prominent and dominant. As a government figure who leads the sub-district level, the sub-district head has the authority to initiate and coordinate the process of forming the MAMI PAPI policy. The sub-district head acts as the main policy maker who determines the direction and goals of MAMI PAPI. The driving factor is the unity of all SKPDs in making the public service mall program a success, while the inhibiting factor is the absence of a previously prepared budget.